Work stress among long-distance coach drivers : a survey and correlational study - Raggatt, Peter T.F. [Verfasser] (My University, 1991)
"This paper presents findings from an Australian survey of work conditions, coping behaviors and stress among 93 long-distance coach drivers. A tripartite model of coach driver stress is presented. The model proposes that the impacts of job demands (e.g. driving hours) on work-related stress outcomes (e.g. doctor visits) are mediated by a set of maladaptive coping behaviors and responses (e.g. stimulant use, speeding). Correlational analyses of the survey data provided general support for the model. Results suggested that long driving hours provide the single best predictor of maladaptive behaviors such as stimulant use and sleep disturbance among the drivers. The maladaptive behaviors, in turn, consistently predicted stress outcomes such as doctor visits and symptom reports." (author's abstract) ((en)) Der Beitrag stützt sich auf eine australische Studie zu den Arbeitsbedingungen und der Stressbewältigung von LKW-Fahrern. Es wird insbesondere untersucht, welche vermittelnden Faktoren (wie Gebrauch von anregenden Mitteln, schnelles Fahren) zwischen den Arbeitsanforderungen (z.B. gefahrene Stunden) und den Folgen der Arbeitsbelastung (z.B. Arztbesuch) bestehen. (IAB)
Arbeitsbelastungen bei LKW-Fernfahrern - Ein Überblick und eine Korrelationsanalyse
Keywords: S 6.4.2.1 Verkehrsberufe (inkl. Nachrichtenverkehr); T 4.8 Arbeitswissenschaften; G 2.3 Wandel von Arbeit & Wirtschaft; Berufskraftfahrer; Arbeitsbelastung; Stressbewältigung; Berufsproblem; Quantitative Angaben